Transnational families and the family nexus: perspectives of Indonesian and Filipino children left behind by migrant parent(s) - Graham, Elspeth (2012)
As a significant supplier of labour migrants, Southeast Asia presents itself as an important site for the study of children in transnational families who are growing up separated from at least one migrant parent and sometimes cared for by ‘other mothers’. Through the often-neglected voices of left-behind children, we investigate the impact of parental migration and the resulting reconfiguration of care arrangements on the subjective well-being of migrants’ children in two Southeast Asian countries, Indonesia and the Philippines. We theorise the child’s position in the transnational family nexus through the framework of the ‘care triangle’, representing interactions between three subject groups— ‘left-behind’ children, non-migrant parents/other carers; and migrant parent(s). Using both quantitative (from 1010 households) and qualitative (from 32 children) data from a study of child health and migrant parents in Southeast Asia, we examine relationships within the caring spaces both of home and of transnational spaces. The interrogation of different dimensions of care reveals the importance of contact with parents (both migrant and nonmigrant) to subjective child well-being, and the diversity of experiences and intimacies among children in the two study countries.